Principal’s Leadership Strategy in Strengthening Teacher Competencies through Gawi Manuntung Philosophy at SMK Negeri 2 Banjarbaru and SMK Negeri 4 Banjarbaru - Sabrina Maulida; Husnul Madihah; Agustina Rahmi (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study explores principals’ leadership strategies in strengthening teacher competencies through the integration of Gawi Manuntung values at SMK Negeri 2 Banjarbaru and SMK Negeri 4 Banjarbaru. Gawi Manuntung, a local wisdom of the Banjar community, reflects task completion, responsibility, discipline, and togetherness. This research used a qualitative case study approach, with data collected through in depth interviews, participatory observation, and documentation involving principals, vocational teachers, and general subject teachers. The findings show that Gawi Manuntung has been internalised not only as a cultural motto but also as part of school management and daily work culture. Its implementation follows B.F. Skinner’s behavioural reinforcement theory through positive reinforcement, negative reinforcement, and educational punishment, including rewards, trust, training, reduced supervision, mentoring, and corrective feedback. These strategies strengthen teachers’ pedagogical, professional, personal, and social competencies. The study also shows that transformational leadership supports this process by positioning principals as role models and culture builders. Integrating structural policies with local cultural values creates a meaningful, contextual, and sustainable educational ecosystem.